Peran Guru PAI Dalam Menanamkan Nilai-Nilai Islam Berbasis Multikultural Di Sekolah - Muslikhin Muslikhin (Institut Agama Islam Negeri Bengkulu, 2019)
With Multicultural education activities that prioritize culture or values in general and globally after social conflicts and prevention in schools, it is expected that as an effort to build a more harmonious life order, based on mutual respect, respect, diversity and promote the principles of humanity and social justice, especially in the education or school environment. Which contains the values of Islam in multicultural education, so students can practice it and understand it so that things that are not desired can be avoided. This is inseparable from the role of PAI teachers in delivering material in class. The main purpose of Multicultural Education is a matter of changing the approach of learning and learning towards providing equal opportunities for each student. So, nothing is sacrificed for the sake of unity. The role of PAI teachers in instilling Islamic values in multicultural education, with a democratic attitude, and trying their best to instill in order to be able to appreciate the differences that exist in students.